Respostas

2014-06-15T14:45:04-03:00
se (a-b)²=16 e a² + b² = 106, calcule bo valor de ab/3

(a-b)² = 16
(a-b)(a-b) = 16
a² -ab- ab + b² = 16
a² - 2ab + b² = 16


a² + b² = 106  (isolar o a²)
a² = 106 - b²

a² - 2ab + b² = 16 ------------------- (agora substituir o a²)
(106 - b²) - 2ab + b² = 16
106 - b² - 2ab + b² = 16
-b² + b² + 106 - 2ab = 16
      0     + 106 - 2ab = 16

106 - 2ab = 16
- 2ab = 16 - 106
- 2ab = - 90
ab = - 90/-2
ab = + 90/2
ab = 45

calcule bo valor de ab/3

para    ab = 45
ab/3

  ab           45
------  -=  --------
   3             3

ab = 45: 3
ab = 15